THE EFFECT OF NUMBERED HEADS TOGETHER LEARNING MODEL ON STUDENTS’ MATHEMATICAL PROBLEM SOLVING ABILITY - Muhammad Riansyah; Desrina Hardianti; Suryatul Aini Asyhara (Hipotenusa Journal of Research Mathematics Education (HJRME), 2023)
The purpose of this study was to determine the effect of the numbered head together learning model on students’ mathematical problem solving abilities at MTs Unwanul Falah Kupang Rejo, Punduh Pidada District, Pesawaran Regency. This study used quasi-experimental. The population of this study were 70 students at class VIII in MTs Unwanul Falah Kupang Rejo, Punduh Pidada District, Pesawaran Regency in Academic Year 2019/2020. The sample was taken by using non-probability sampling method. The hypothesis test of this study used the t test. The result of the use of the NHT learning model had made a significant contribution to students’ mathematical problem solving abilities ub mathematics. The results obtained by students’ problem solving skills after being given an NHT learning model were higher than the control class wich was not given the NHT. This could be seen from students who are given the NHT. There was an effect of learning numbered head together on student’ mathematical problem solving abilities in at class VIII in MTs Unwanul Falah Kupang Rejo, Punduh Pidada District, Pesawaran Regency In Academic year 2019/2020.